Analyzing effect of temperature variation on skin Sub-layers using finite element approach - MONA DWIVEDI,; USHA CHOUHAN, (International Journal of Pharma and Bio Sciences, 2017)
The temperature distribution in human body regulates variety of biological mechanism. Human Skin is a very complex structure and abnormality in temperature of various layer of skin play important role for curing and treatment diseases like tumor, cancer etc. The eight layers of human skin namely stratum corneum, stratum lucidum, stratum granulosum, stratum spinosum, stratum germinativum, papillary, reticular and subcutaneous tissue are considered for the study. A one dimensional Finite element model is developed to study the temperature distribution involving blood circulation rate, metabolic heat generation and thermal conductivity in human skin. A MATLAB program has been developed to obtain the numerical results.